(untitled) (European Science Methodical Journal, 2024)
In this article, the activities of creative intellectuals in the years of independence, including the work of intellectual women working in the education system, historical researches in the higher education system of Uzbekistan, their attitudes and solutions to current problems arising in the field in the era of complex globalization, as well as in international cooperation relations His work and achievements are highlighted.